Star Performers in Twenty‐First Century Organizations. Issue 2 (17th September 2013) - Aguinis, Herman; O'Boyle, Ernest
<x xml:space="preserve">Abstract</x> We argue that changes in the nature of work in 21st‐century organizations have led to the emergence of star performers—a few individuals who contribute a disproportionate amount of output. We describe how stars negate the long‐held belief that the distribution of individual performance is normal and, instead, suggest an underlying power law distribution. In addition, we offer 9 propositions to guide future empirical research on star performers and an underlying power law distribution of individual performance. We describe how the presence of stars is likely to affect all individual‐, team‐, and firm‐level management theories addressing individual performance directly or indirectly, but focus on specific implications for those addressing human capital, turnover, compensation, downsizing, leadership, teamwork, corporate entrepreneurship, and microfoundations of strategy. In addition, we discuss methodological considerations necessary to carry out our proposed research agenda. Finally, we discuss how a consideration of star performers has important implications for management practice.